Efficient photocatalytic water reduction by a cobalt(ii) tripodal iminopyridine complex. Issue 1 (30th November 2017) - Leung, C.-F.; Cheng, S.-C.; Yang, Y.; Xiang, J.; Yiu, S.-M.; Ko, C.-C.; Lau, T.-C.
Abstract : Enhanced reactivity is observed in a cobalt tripodal iminopyridine WRC bearing a metal active site with a trigonal pyramidal coordination geometry. Abstract : The visible light-driven catalytic water reduction by a cobalt(ii ) tripodal iminopyridine complex [Co(tachpy3 )](ClO4 )2 (1 ) (tachpy3 = cis, cis -1, 3, 5-tris(pyridine-2-carboxaldimino)-cyclohexane) has been investigated in aqueous acetonitrile. The catalysis is found to be homogeneous and an impressive H2 TON of 16 440 has been achieved, which is far better than that by a structurally related complex [Co(trenpy3 )](ClO4 )2 (2 ) (trenpy3 = tris-[4-(2-pyridyl)-3-azabut-3-enyl]amine) bearing identical donor groups. A comparison between the two complexes reveals that the catalytic properties are sensitive to the change in ligand rigidity and thus the coordination geometry, as reflected by their respective reaction potentials and H2 TONs. The catalysis of1 proceeds via a penta-coordinate species formed by the protonation of the corresponding Co I state. The results in spectroscopic and electrochemical studies are supplemented by DFT computation.